Examining Map Projection Distortions using Geospatial Web Tools - S. Gupta; T. Tienaah; E. Stefanakis (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
This paper presents a geospatial web application developed recently to support the teaching needs of sophomores at the University of New Brunswick on basic mapping concepts focussing on map projections. The application was built using multiple open source web programming tools and base maps; and it consists of a visualizer and a set of web services.